The Relationship between Physical Activity Implementation and Quality of Life for the Elderly During the COVID-19 Pandemic in Samarinda - Gracia Herni Pertiwi; Yovita Erin Sastrini (Budapest International Research and Critics University, 2022)
The first case of coronavirus disease-19 (COVID-19) occurred in Indonesia in 2020. Transmission of this disease occurs through human-to-human transmission. In the elderly, physical and mental health is a determinant in the quality of life. Physically it is estimated that quarantine rules or restrictions on physical activity can cause a decrease in the need for daily activities in the elderly. The results of initial interviews conducted on three elderly people obtained information that during the pandemic they spent a lot of time at home, so they sometimes felt bored and lonely. Research to find out the relationship between physical activity implementation and quality of life for the elderly during the COVID-19 pandemic in Samarinda. This study is a cross-sectional study. This study involved 34 elderly people aged 45 years and over from March to April 2022 in the Elderly Group of the Stasi Girirejo Samarinda. Data on the characteristics, physical activity implementation, and quality of life of the elderly were obtained through structured interviews with questionnaires using the physical activities scale for the elderly (PASE) and world health organization quality of life BREF (WHOQOL-BREF) questionnaires. The types of data analysis used are frequency distribution, percentage, and fisher exact test. Fisher exact test results show that there is no relationship between physical activity implementation and quality of life of the elderly.